2021
DOI: 10.37387/ipc.v9i2.232
|View full text |Cite
|
Sign up to set email alerts
|

Generación y segregación de residuos sólidos domiciliarios durante la cuarentena por Covid-19 en Panamá, estudio de caso

Abstract: La pandemia del Covid-19 ha provocado la declaratoria de cuarentenas en casi todos los países del mundo, en Panamá se mantuvo un confinamiento estricto entre los meses de marzo y setiembre. A pesar de la importancia de la gestión de los residuos sólidos en las ciudades la información sobre el impacto de la cuarentena en la generación y composición de residuos no ha sido lo suficientemente recopilada y difundida. En este estudio se presenta una metodología innovadora para recolectar información sobre los residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Likewise, Fan et al ( 2021 ) reported a 23% decline in municipal solid waste in Shanghai. In Latin America, the application of this methodology also evidenced a reduction in the generation of household waste in Lima (Peru) (Requena et al 2020 ), Panama (Requena Sanchez et al 2021a ) and Honduras (Requena Sanchez et al 2021b ). This decrease may be due to a lower purchasing power of families caused by the economic recession resulting from the quarantine (Ikiz et al 2021 , Naughton 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Fan et al ( 2021 ) reported a 23% decline in municipal solid waste in Shanghai. In Latin America, the application of this methodology also evidenced a reduction in the generation of household waste in Lima (Peru) (Requena et al 2020 ), Panama (Requena Sanchez et al 2021a ) and Honduras (Requena Sanchez et al 2021b ). This decrease may be due to a lower purchasing power of families caused by the economic recession resulting from the quarantine (Ikiz et al 2021 , Naughton 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…All these layers are made by TNT, usually of the spunbond or spunlance polypropylene type. Likewise, Requena et al (2021) mention that it is important to take this data into account due to the risk of biocontamination presented by waste such as masks and gloves.…”
Section: Percentage Of Mask Waste Per Monthmentioning
confidence: 99%